2019
DOI: 10.1097/bpo.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Physeal and Subphyseal Distraction Osteogenesis in Atrophic-type Congenital Pseudarthrosis of the Tibia: Efficacy and Safety

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In 1958, Ring [11] first reported the physeal distraction osteogenesis technology. Because there is a risk of knee joint infection and bone bridge when the proximal tibial epiphyseal plate is lengthened [11][12][13], children's orthopedics doctors rarely carry out this operation. However, in 2013, Vlad [14] and other scholars reported that the physeal distraction Is epiphyseal plate lengthening good to treat CPT patients?…”
Section: Discussionmentioning
confidence: 99%
“…In 1958, Ring [11] first reported the physeal distraction osteogenesis technology. Because there is a risk of knee joint infection and bone bridge when the proximal tibial epiphyseal plate is lengthened [11][12][13], children's orthopedics doctors rarely carry out this operation. However, in 2013, Vlad [14] and other scholars reported that the physeal distraction Is epiphyseal plate lengthening good to treat CPT patients?…”
Section: Discussionmentioning
confidence: 99%
“…The reasons may be as follows: (1) The treatment of children with CPT is a long-term process. 13 , 14 It requires many operations and the postoperative wearing of an external fixator for a long time. The illness reoccurs easily, infection is common and caregivers have concerns about the prognosis of children with psychological problems; (2) Care for children with CPT requires substantial human and material resources from the family, the costs of surgery and treatment are high, postoperative recovery is uncertain and the need to respond to possible complications and refractures may hinder the formation of family resilience; (3) Related studies have found that with long-term surgery, an unfamiliar environment, long-term postoperative breaking and pain and many other factors, children who have CPT surgery have serious medical fears and strong physiological and psychological stress reactions, which seriously affects their safety, the surgical efficacy and postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone transport technique, after excision of the pathological bone specimen, can be used to restore the axis and the length discrepancy of the pseudoarthrotic tibia. The Ilizarov method has increased the rate of successful management of the tibial pseudoarthrosis [37,38].…”
Section: Osseous Involvement Of Long Bones 31 Tibiamentioning
confidence: 99%